STRATEGI, MANAJEMEN MODAL KERJA, DAN KINERJA KEUANGAN PADA SIKLUS HIDUP PERUSAHAAN SEKTOR BASIC MATERIAL DI BURSA EFEK INDONESIA - Niken Rosiyanti, (2022)
The purpose of this study is to look at the influence of working capital strategies and working capital management on financial performance according to the life cycle stages of basic material sector companies on the Indonesia Stock Exchange during 2011-2020. The use of purposive sampling resulted in 51 companies as research samples. Excel 2016 used excel 2016 to analyze data and IBM SPSS 22 for regression analysis hierarchy linear method. Use Sig. 0.05 results that working capital strategy and working capital management affect financial performance at the introduction and mature stage of the company's life cycle. .